Uji Kinerja Bioeraktor Hibrid Anaerob Dua Tahap Pada Pengolahan Limbah Cair Industri Sagu Dengan Variabel Beban Kejut (Shock Loading) - Apriadi Rio; Adrianto Ahmad; Amun Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The wider the area of sago palm in Indonesia, the more rapid development of the industry in increasing the production of sago. Industrial production sago produce wastewater with high organic matter content, if discharged directly into the water body will continually degrade water quality and environmental pollution. Thus, needs to be processed with a technology prior to disposal, wastewater treatment technology is a two-stage anaerobic bioreactor hybrid. The purpose of this study is to test the stability and performance of the two-stage anaerobic bioreactor hybrid stone in anticipation of media change suddenly arriving feed flow rate due to the increasing production of sago industry. Hybrid anaerobic bioreactor working volume of two stages used in this study was 10 L in the first bioreactor and 20 L in the second bioreactor. Operation was carried out by giving a shock loads increasing the feed flow rate suddenly by 50%, 100% and 150% for 6 hours in the first bioreactor, and then returned to the first bioreactor flow rate was 5 L/day. The results showed that the two-stage anaerobic hybrid bioreactor stone mediated able to anticipate fluctuations in the production of industrial wastewater discharge sago with the feed flow rate suddenly by 50%, 100% and 150% indicates that the system recovery time of two stage anaerobic bioreactor hybrid was faster with a span of 5 to 6 days. The highest COD removal occurred at shock loads of 100% of 3.750 mg/L.Keywords: Anaerobic , COD Hybrid Anaerobic Bioreactor, Sago Wastewater, Shock Loading, Two Stage.